Unravelling the myth – The use of Decisions Support Systems in marine management. (January 2018) - Bolman, Bas; Jak, Robbert G.; van Hoof, Luc
Abstract: Over the past decade the development of Decision Support Systems (DSSs) for the management of seas and oceans has increased rapidly. These DSSs take many shapes and forms and their application in actual decision processes varies widely. In order to appreciate the multitude of DSSs a theoretical framework was developed to evaluate the appropriateness of a given DSS for marine management decision processes with the aim to guide developers in building better DSSs. This framework was applied to a number of DSSs recently developed for marine management. Many tools, promoted to be DSSs, are in fact science driven models that do not address the basic problems and challenges of decision making. Of course, by providing information and making scientific data available in order to make scientifically informed decisions, science does have a role in environmental and ecosystem based decision making, yet the contribution of science to decision making in marine management by these models is highly overrated. In order for a DSS to be relevant and useful it must be aligned with the needs of the decision maker and provide available data in such a way that it becomes information in the decision process. The framework used to evaluate the DSSs can be a helpful tool to apply throughout the development of a DSS in order to enhance the effectiveness/usefulness of these tools through the engagement of end-users and stakeholders. Highlights: This paper aims to guide developers in building better DSSs for marine management. A theoretical framework was developed and applied to a set of DSS papers. Many DSSs are science driven models that do not address the basic problems of decision making. For a DSS to be relevant and useful it must be aligned with the needs of the decision maker. The theoretical framework can be a helpful tool for DSS developers by engaging end-users and stakeholders.